5(x-3)+(x-4)=5x-6

Simple and best practice solution for 5(x-3)+(x-4)=5x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)+(x-4)=5x-6 equation:


Simplifying
5(x + -3) + (x + -4) = 5x + -6

Reorder the terms:
5(-3 + x) + (x + -4) = 5x + -6
(-3 * 5 + x * 5) + (x + -4) = 5x + -6
(-15 + 5x) + (x + -4) = 5x + -6

Reorder the terms:
-15 + 5x + (-4 + x) = 5x + -6

Remove parenthesis around (-4 + x)
-15 + 5x + -4 + x = 5x + -6

Reorder the terms:
-15 + -4 + 5x + x = 5x + -6

Combine like terms: -15 + -4 = -19
-19 + 5x + x = 5x + -6

Combine like terms: 5x + x = 6x
-19 + 6x = 5x + -6

Reorder the terms:
-19 + 6x = -6 + 5x

Solving
-19 + 6x = -6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-19 + 6x + -5x = -6 + 5x + -5x

Combine like terms: 6x + -5x = 1x
-19 + 1x = -6 + 5x + -5x

Combine like terms: 5x + -5x = 0
-19 + 1x = -6 + 0
-19 + 1x = -6

Add '19' to each side of the equation.
-19 + 19 + 1x = -6 + 19

Combine like terms: -19 + 19 = 0
0 + 1x = -6 + 19
1x = -6 + 19

Combine like terms: -6 + 19 = 13
1x = 13

Divide each side by '1'.
x = 13

Simplifying
x = 13

See similar equations:

| 2xy+3xy=5xy | | 0.5-0.2=9.3 | | 72/u=8 | | 6x+10=-4-4x | | 4x+3=3+6x-8 | | 5x+8=66 | | 480/y=24 | | 5log^5(9-x)=6 | | 5(x-3)=13x-5 | | 100=10x+5y+0.5z | | 10m-13=57 | | g/8-5=8 | | 1/5x-2=15 | | 2+7x=8+x | | 8(x+3)=2x+66 | | x+1=10-8 | | 10z+4=54 | | 2+10x=-7x | | 6x+15=7x+13 | | w=67-21 | | 10+x=11+x | | 4=r^2/3 | | 2v-56=34 | | 12+4(w-5)=16-2w | | 7-7x-4=-71+5x-10 | | n+50=110 | | 2.2x+63=3.7x+18 | | 4c-13=23 | | n+42=123 | | -4y=-12x+32 | | 42+n=123 | | 0.6x+1.9=0.9x-0.2 |

Equations solver categories